Simplify the following surd expressions
a) 7V3 - 2V3 + V3 - 3V3
b) 5V7 +4V7 – 8V7
![Simplify the following surd expressions a 7V3 2V3 V3 3V3 b 5V7 4V7 8V7 class=](https://us-static.z-dn.net/files/dce/a28c476f97990eb1eacf4cd9ec699a9b.png)
Step-by-step explanation:
[tex]a) \: 7 \sqrt{3} - 2 \sqrt{3} + \sqrt{3} - 3 \sqrt{3} [/tex]
[Taking sq.root 3 common]
[tex] = (7 - 2 + 1 - 3) \sqrt{3} [/tex]
[tex] = (8 - 5) \sqrt{3} [/tex]
[tex] = 3 \sqrt{3} (ans)[/tex]
[tex]b) \: 5 \sqrt{7} + 4 \sqrt{7} - 8 \sqrt{7} [/tex]
[Taking sq.root 7 common]
[tex] = (5 + 4 - 8) \sqrt{7} [/tex]
[tex] = (9 - 8)\sqrt{7} [/tex]
[tex] = 1 \sqrt{7} [/tex]
[tex] = \sqrt{7} (ans)[/tex]